Grade-Level Differences in Teacher Feedback and Students’ Self-Regulated Learning - Guo, Wenjuan (Frontiers in Psychology, 2020)
This study investigated grade-level differences in teacher feedback, students’ self-regulated learning (SRL), and their relationship. Secondary students participated in the study (N = 1,260; 430 10th-, 460 11th-, and 370 12th-graders). Latent factor mean difference analyses suggested that teacher feedback and students’ SRL level varied across grades. Comparatively, 10th-grade teachers were perceived to provide verification feedback, scaffolding feedback, and praise most frequently; 12th-grade teachers were perceived to provide directive feedback and criticism most frequently; and 11th-grade teachers were perceived to provide all types of feedback least frequently. Students’ SRL generally declined as they aged. Results from three-group structural equation modeling indicated that praise generally exhibited the strongest correlations with SRL regardless of grade level; directive feedback was negatively correlated with 10th graders’ SRL but positively correlated with the SRL of 11th and 12th graders; scaffolding and verification feedback were positively correlated with 11th graders’ SRL; and criticism had small correlations with SRL, regardless of grade level.